Determining suitable fish to monitor plastic ingestion trends in the Mediterranean Sea. (April 2019) - Bray, Laura; Digka, Nikoletta; Tsangaris, Catherine; Camedda, Andrea; Gambaiani, Delphine; de Lucia, Giuseppe Andrea; Matiddi, Marco; Miaud, Claude; Palazzo, Luca; Pérez-del-Olmo, Ana; Raga, Juan Antonio; Silvestri, Cecilia; et al.
Abstract: The presence of marine litter is a complex, yet persistent, threat to the health and biodiversity of the marine environment, and plastic is the most abundant, and ubiquitous type of marine litter. To monitor the level of plastic waste in an area, and the prospect of it entering the food chain, bioindicator species are used extensively throughout Northern European Seas, however due to their distribution ranges many are not applicable to the Mediterranean Sea. Guidance published for the Marine Strategy Framework Directive suggests that the contents of fish stomachs may be analyzed to determine trends of marine plastic ingestion. In order to equate transnational trends in marine plastic ingestion, the use of standardized fish species that widely occur throughout the basin is favoured, however for the Mediterranean Sea, specific species are not listed. Here we propose a methodology to assess how effective Mediterranean fish species, that are known to have ingested marine plastic, are as bioindicators. A new Bioindicator Index (BI) was established by incorporating several parameters considered important for bioindicators. These parameters included species distribution throughout the Mediterranean basin, several life history traits, the commercial value of each species, and the occurrence of marine litter in their gut contents. By collecting existing data for Mediterranean fish, ranked scores were assigned to each trait and an average value (BI value) was calculated for each species. Based on their habitat preferences, Engraulis encrasicolus (pelagic), Boops boops (benthopelagic), three species of Myctophidae ( Hygophum benoiti, Myctophum punctatum and Electrona risso ) (mesopelagic), Mullus barbatus barbartus (demersal) and Chelidonichthys lucerna (benthic), were identified as currently, the most suitable fish for monitoring the ingestion of marine plastics throughout the Mediterranean basin. The use of standardized indicator species will ensure coherence in the reporting of marine litter ingestion trends throughout the Mediterranean Sea. Graphical abstract: Image 1 Highlights: An index describes suitable marine plastic fish bioindicators in the Mediterranean. European anchovy is well suited to monitor plastic trends in pelagic environments. Boops boops appears the most adept plastic bioindicator for benthopelagic habitats. For marine demersal habitats, Mullus barbatus barbatus is a suitable bioindicator. The work contributes to standardization of Mediterranean monitoring protocols. Abstract : Using a novel index, seven species of fish were identified as the most suitable to monitor marine plastic ingestion trends in the Mediterranean Sea.